Cutaneous traction as a complement to the parascapular flap in major cancer loss: case report - Marcelo Rosseto; Luana Graziela Batista; Franco Silva Martinez; Blanca Silva Martinez; Carolina Maria Startari Sacco; Letícia Suemi Arakaki; Micael Viana Azevedo; Luiz Fernando Alves de Oliveira (Revista Brasileira de Cirurgia Plástica)
Introduction: Squamous cell carcinoma (SCC) is a malignant epidermal keratinocyte tumor closely related to sun exposure. When diagnosed, through biopsy, its staging, tumor resection with oncological safety margins must be performed, and lymph node dissection and treatment of metastases, if present, may be performed. Case Report: Skin traction is reported as a complement to the parascapular flap, used reconstructively after the excision of a large SCC in the left shoulder. Conclusion: The technique used proved effective for the satisfactory correction of large dehiscence in the postoperative period of the parascapular flap, promoting partial closure of the defect, reduced time to perform, and correction of the residual defect in a single step.